DIAGNOSTIC VALUE OF INFLAMMATORY BLOOD PATTERNS IN VERIFICATION OF UNCONTROLLED COURSE OF BRONCHIAL ASTHMA IN CHILDREN - Bezrukov, L.O.; Tarnavska, S.I.; Shevchuk, N.M.; Kretsu, N.M. (World of Medicine and Biology, 2018)
On the basis of complex clinical-paraclinical examination of 120 children, the diagnostic value of inflammatory blood patterns was studied for the prognosis of uncontrolled course of bronchial asthma. It was established that in the presence of hypergranulocytic inflammatory blood pattern, the chances of registration of clinical manifestations of the severity of the disease increased in the range of 1.5-12.7 times, along with an increase in the chances of a distinct lability of the bronchi in 14.1 times compared with the hypogranulocytic phenotype. At the same time, the isolated use of the study of only inflammatory blood patterns for verifying the achievement or loss of control of the disease has insufficient information due to a significant proportion of false positive and false negative results.